Interaction Of Propylthiouracil With Model Systems Generating A Superoxide Radical - Maria Valcheva-Traykova; Trayko Traykov; Georgeta Bocheva (Journal of Biomedical & Clinical Research)
Propylthiouracil is used against Grave's Disease and for developing animal models of hypothyroidism. Apart from depressed metabolism, free radical-induced tissue damage has been registered as an effect from this drug. Superoxide is essential for generation of free radicals in tissues. The mutual effects of Propylthiouracil and superoxide radical have not been well investigated.The in vitro effects of Propylthiouracil on the free radicals in three model systems generating superoxide were measured using luminol-dependent chemiluminescence and spectrophotometry. The drug did not affect the formation of free radicals in the presence of potassium superoxide and in pyrogallol-oxygen solutions, while in the presence of the xanthine/xanthine oxidase system a distinct prooxidant effect was registered. The investigation of the system propylthiouracil/xanthine oxidase showed mild free radicals formation along with decreasing intensities of the drug's UV-specter.Our in vitro investigation indicated that, along with the transformation of xanthine to uric acid over xanthine oxidase, some free radicals may be produced due to the interaction of propylthiouracil with the enzyme. It was proposed that this might contribute to the in vivo free radicals-induced tissue damage observed in the presence of propylthiouracil.